Effects of Dietary Nutrients on Fatty Liver Disease Associated With Metabolic Dysfunction (MAFLD): Based on the Intestinal-Hepatic Axis - Yao, Nan; Yang, Yixue; Li, Xiaotong; Wang, Yuxiang; Guo, Ruirui; Wang, Xuhan; Li, Jing; Xie, Zechun; Li, Bo; Cui, Weiwei (Frontiers in Nutrition, 2022)
Non-alcoholic fatty liver disease (NAFLD) has recently become the most common liver disease with a global prevalence of over 25% and is expected to increase. Recently, experts have reached a consensus that "fatty liver disease associated with metabolic dysfunction or MAFLD" may be a more appropriate and inclusive definition than NAFLD. Like the former name NAFLD, MAFLD, as a manifestation of multiple system metabolic disorders involving the liver, has certain heterogeneity in its pathogenesis, clinical manifestations, pathological changes and natural outcomes. We found that there is a delicate dynamic balance among intestinal microflora, metabolites and host immune system to maintain a healthy intestinal environment and host health. On the contrary, this imbalance is related to diseases such as MAFLD. However, there are no clear studies on how dietary nutrients affect the intestinal environment and participate in the pathogenesis of MAFLD. This review summarizes the interactions among dietary nutrients, intestinal microbiota and MAFLD in an attempt to provide evidence for the use of dietary supplements to regulate liver function in patients with MAFLD. These dietary nutrients influence the development and progression of MAFLD mainly through the hepatic-intestinal axis by altering dietary energy absorption, regulating bile acid metabolism, changing intestinal permeability and producing ethanol. Meanwhile, the nutrients have the ability to combat MAFLD in terms of enriching abundance of intestinal microbiota, reducing Firmicutes/Bacteroidetes ratio and promoting abundance of beneficial gut microbes. Therefore, family therapy with MAFLD using a reasonable diet could be considered.